Primary pulmonary histiocytic sarcoma with CNS metastasis: a case report and molecular profiling insights - Chen, Kai; Zhang, Lei; Wu, Ruotong; Wei, Jingxian; Yang, Kaige; Luo, Chenghua; Zhang, Haijun; Tao, Lin; Yang, Lan; Meng, Lian; Nong, Weixia; Hu, Jianming (Frontiers in Oncology, 2026)
Histiocytic sarcoma (HS), reclassified in the WHO fifth edition as a Histiocytic/dendritic cell neoplasms, represents a rare hematopoietic malignancy with extranodal predominance and aggressive clinical behavior. This study reports the case of a 53-year-old female diagnosed with primary pulmonary HS, who presented with a 60-mm mass in the right middle lobe and later developed fatal brain metastases. Using a combination of pathology, whole-exome sequencing, and fusion gene analysis, we identified key molecular drivers of tumor development and spread. Major findings include the concurrent activation of the RAS/MAPK and PI3K/mTOR pathway activation (118 combined gene variants), TP53 biallelic inactivation, HLA locus alterations, and persistent LOC285045 fusions. Drug sensitivity profiling suggested potential responses to sunitinib and MEK inhibitors. By comparing this case with nine other reported cases of lung HS, we found that lung HS has a significantly worse survival (p=0.03) than HS at other sites. A high cell growth rate (Ki-67 >30%) and large tumor size (>50 mm) were identified as critical indicators of poor prognosis.